Allusions and Omissions in Augustine’s Confessions - Benjamin Elliott (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2024)
This paper discusses possible biblical allusions and omissions in Augustine’s Confessions, arguing that the themes he presents can be understood with greater nuance if viewed in light of not only the scriptural passages he chooses to support them but also the verses from the immediate context, which he omits. The paper will examine four examples from within the Confessions: the way that in the Confessions but not elsewhere, he only utilizes the second half of James 1:17, eliding the phrase ‘Father of lights,’ his use of the term unam for his concubine, his depiction of his mother Monnica like the apostle Paul, and possible reasons for his elision of portions of the prologue to John. As a result, this paper has offered four possible instances of Augustine omitting, or only allusively referring to, specific scriptures throughout the Confessions: his omission of God as the Father of lights when referencing James 1, his allusion to the una columba of the Canticle of Canticles in describing his concubine, his undertone of Pauline episodes in recounting the tale of Monnica's arrival in Rome, and finally his omission of John the Baptist from It has been suggested that, in each of these cases, a deeper grasp of the parts of the Bible that Augustine has left out can help us comprehend the major arguments that he has made in more depth.